A Microfluidics Workflow for Sample Preparation for Next-Generation DNA Sequencing. (April 2019) - Snider, Adam; Nilsson, Michael; Dupal, Mark; Toloue, Masoud; Tripathi, Anubhav
Next-generation sequencing technology requires amplified, short DNA fragments with known end sequences. Samples must undergo processing steps, including extraction and purification of genomic DNA (gDNA), fragmentation, end repair, adapter ligation, and amplification, to prepare a sequencing library. The process of sample preparation requires careful control of temperature and buffer conditions, as well as the stringent removal of contaminants. As a result, library preparation methods are often plagued by sample loss, long protocol times, numerous manual steps, and high cost. We attempt to understand and optimize each step of sample preparation on a microfluidic platform using magnetic bead motion through channels containing immiscible phases. Our platform integrates all steps associated with library preparation with no buffer exchanges and utilizes just 30–60 µL of reagents. Our chip shows a sixfold improvement in yield compared with an affinity spin column when capturing gDNA from samples of 50 ± 4 MCF-7 cells. Finally, we show whole-genome shotgun sequencing results from 660 pg of human gDNA, in which >93 ± 1% of reads map to a reference genome at or above 99.9% confidence, matching a commercially available sample preparation kit optimized for low-cell-count samples.